2020
DOI: 10.1371/journal.ppat.1009067
|View full text |Cite
|
Sign up to set email alerts
|

A single Na+-Pi cotransporter in Toxoplasma plays key roles in phosphate import and control of parasite osmoregulation

Abstract: Inorganic ions such as phosphate, are essential nutrients required for a broad spectrum of cellular functions and regulation. During infection, pathogens must obtain inorganic phosphate (Pi) from the host. Despite the essentiality of phosphate for all forms of life, how the intracellular parasite Toxoplasma gondii acquires Pi from the host cell is still unknown. In this study, we demonstrated that Toxoplasma actively internalizes exogenous Pi by exploiting a gradient of Na+ ions to drive Pi uptake across the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 87 publications
4
14
0
Order By: Relevance
“…On the other hand, disruption of Tg G6PDHs will block NADPH synthesis but maintain the intact downstream pathway. A previous study has reported that Toxoplasma expresses a phosphate transporter that plays a crucial role in the phosphate import [ 35 ]. There may be transporters in the parasite membrane to import 6-phosphogluconate and possibly other host-derived PPP intermediates that can sustain (low-level) synthesis of NADPH in the Δg6pdh1Δg6pdh2 strain.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, disruption of Tg G6PDHs will block NADPH synthesis but maintain the intact downstream pathway. A previous study has reported that Toxoplasma expresses a phosphate transporter that plays a crucial role in the phosphate import [ 35 ]. There may be transporters in the parasite membrane to import 6-phosphogluconate and possibly other host-derived PPP intermediates that can sustain (low-level) synthesis of NADPH in the Δg6pdh1Δg6pdh2 strain.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). This protein was named TgPiT, and it has Na + -dependent inorganic phosphate transport activity, as reported recently ( 35 ). TgPiT is widely present and conserved in apicomplexan parasites, including Plasmodium ( Fig.…”
Section: Resultsmentioning
confidence: 72%
“…The Toxoplasma ortholog (TgPiT) of PfPiT shows similar phosphate-transporting activity. TgPiT deletion results in reduced inorganic phosphate import and polyphosphate synthesis ( 35 ). Unexpectedly, the Δ Tgpit mutants only showed a modest growth defect and virulence attenuation ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The later identification of VTC as the key mediator of PolyP synthesis in fungi vacuoles and protozoan acidocalcisomes comprises one more similarity between these 2 models. Further studies using vtc mutants confirmed that PolyP storage in acidocalcisomes is important for the virulence and/or survival under infection conditions of trypanosomatid and apicomplexan protozoans [ 30 33 ]. More recently, a conserved role for InsP in regulating Pi homeostasis by interaction with SPX domains has also emerged in Trypanosoma brucei [ 34 ].…”
Section: Other Pathogens Have Striking Similarities In How They Store...mentioning
confidence: 99%